Figure 3. A, B in Somatic musculature of Tardigrada: phylogenetic signal and metameric patterns - Marchioro, Trevor; Rebecchi, Lorena; Cesari, Michele; Hansen, Jesper Guldberg; Viotti, Giulia; Guidetti, Roberto (Zenodo, 2013)
Figure 3. A, B, musculature of Milnesium cf. tardigradum (A, dorso-lateral view; B, ventro-lateral view). C, D, musculature of Acutuncus antarcticus (C, lateral view; D, ventro-lateral view). Ph, pharynx. Letters and numbers identify the muscle attachment points (see text). Nodes of ventral muscle groups are marked by hexagons; attachment points and nodes of lateral muscle group are marked by squares; attachment points and nodes of dorsal muscle group are marked by circles. A–D, CSLM, maximum projection. B, C, colour coded by depth. Scale bars: A–D = 50 μm. : Published as part of Marchioro, Trevor, Rebecchi, Lorena, Cesari, Michele, Hansen, Jesper Guldberg, Viotti, Giulia & Guidetti, Roberto, 2013, Somatic musculature of Tardigrada: phylogenetic signal and metameric patterns, pp. 580-603 in Zoological Journal of the Linnean Society 169 (3) on page 586, DOI: 10.1111/zoj.12079, http://zenodo.org/record/5291175